2022
DOI: 10.1093/hmg/ddac009
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the genetic mechanism that associates L3MBTL3 to multiple sclerosis

Abstract: Multiple sclerosis (MS) is a complex and demyelinating disease of the central nervous system. One of the challenges of the post-GWAS era is to understand the molecular basis of statistical associations to reveal gene networks and potential therapeutic targets. The L3MBTL3 locus has been associated with MS risk by GWAS. To identify the causal variant of the locus, we performed fine mapping in a cohort of 3440 MS patients and 1688 healthy controls. The variant that best explained the association was rs6569648 (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…31 In addition, it has been concluded that the genetic mechanism of rs740107 associated with MS may involve its effect on L3MBTL3 expression. 29 Taken together, we proposed that L3MBTL3 polymorphisms may play a potential role in CHD development. However, no data have been reported on the relationship between L3MBTL3 polymorphisms and CHD susceptibility.…”
Section: Introductionmentioning
confidence: 77%
See 2 more Smart Citations
“…31 In addition, it has been concluded that the genetic mechanism of rs740107 associated with MS may involve its effect on L3MBTL3 expression. 29 Taken together, we proposed that L3MBTL3 polymorphisms may play a potential role in CHD development. However, no data have been reported on the relationship between L3MBTL3 polymorphisms and CHD susceptibility.…”
Section: Introductionmentioning
confidence: 77%
“…[34][35][36] In addition, it has been concluded that the causal effect associated with MS protection would be the up-regulation of L3MBTL3 expression. 29 Based on these findings, we hypothesized that the protective effect may be attributed to its influence on gene expression. The potential functions of SNPs demonstrated that rs1125970 was associated with the regulation of enhancer histone marks, alterations in motifs, and selected eQTL hits.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MS features encompass neuroinflammation, demyelination, and axonal loss within the CNS [99,100]. Several mechanisms have been proposed to be implicated in the pathophysiology of MS [101][102][103]. Nevertheless, the potential role of BAMs in MS has been only recently investigated [47,104].…”
Section: Bams In Multiple Sclerosismentioning
confidence: 99%